Evaluation of Water Heating Systems Through Life Cycle Assessment - Vechi, Marcel; Ghisi, Enedir (European Journal of Sustainable Development, 2018)
The aim of this study is to evaluate water-heating systems through Life Cycle Assessment (LCA). The method involves the application of LCA for the analysis of the global warming potential of water-heating systems that use electricity, gas or solar energy as input. The analysis was performed for a single-family house and also for a four-storey residential building located in three cities in Brazil. The SimaPro computer programme, widely used in the global market when it comes to LCA, was used. The results showed that for the single-family house, the electric shower head is the option that causes less environmental impact for all cities, followed by the solar heater with electric backup and, finally, gas heater with continuous flow. As for the four-storey residential building, the solar heater was the best alternative, followed by the electric shower head, electric boiler, gas heater with continuous flow and, finally, gas boiler. The use phase was responsible for most of the total impact on most systems except for solar heater. The main conclusion is that, in Brazil, water-heating systems that use electricity and solar energy should be preferred over those that use natural gas. Keywords: Life Cycle Assessment, water-heating systems, environmental impact, buildings, computer simulation, SimaPro